The study of project cargo logistics operation: A general overview - Oktaviani Turbaningsih (Journal of Shipping and Trade (JST), 2022)
The recent renewable energy infrastructure development trend and modular construction concept surge academic interest in the project logistics sector. The project logistics is the transportation processes for oversized cargo, critical and high value, that belong to infrastructures projects; that require specialised stowage, lifting and transporting loaded and discharged at different ports. This study aims to introduce project logistics to the public sector. The author uses the descriptive review to elaborate on the niche problem of project cargo transportation. The flow of project cargo operation from the fabrication yard to the final installation site is discussed in this paper. Planning of project cargo logistics requires an integrated planning approach that considers the following aspects total delivery cost management, end-to-end visibility, transport routing management, variability management, integrated international and domestic workflow, and technical safety consideration. The decision-making for fleet selection should be based on the optimum scenario evaluating the damage's total logistics cost, delivery time, risks and consequences. This study can be a guide to accommodate multidiscipline studies that consider commercial, technical, and safety aspects of project logistics.
Keywords: 650; Project logistics; Port infrastructure; Heavy lifting; Heavy haulage; Out of gauge